DIGITAL TRANSFORMATION OF VOCATIONAL SCHOOL MANAGEMENT: INCREASING SCHOOL ACADEMIC SERVICES EFFECTIVELY? - Sinaga, Josephine Halcynon; Komariah, Aan; Suharto, Nugraha (Jurnal Administrasi Pendidikan, 2024)
The purpose of this article is to find out how management in Vocational High Schools (SMK) in school academic services is in accordance with the current era. The research method used is the literature study method. Data collection techniques by collecting and analyzing documents related to guidelines, management documents in several SMKs in Sukabumi. The school management aspect has reached digital status, although not all indicators of each aspect of school management are digital-based. Three vocational high school managements can be categorized in the digital transformation process. Like the implementation of MIS (Management Information System - MIS) owned by each school, it is already an initial step for digital transformation in the field of school management. School management and academic services that are based on digital technology are profoundly interconnected and effectively increase school academic services. By automating administrative functions, offering real-time access to academic information, and facilitating personalized learning experiences, digital management systems significantly enhance the provision of academic services. These systems not only boost communication, transparency, and efficiency but also enable data-driven decision-making, tailored support, and ongoing enhancement of both teaching and learning processes.